The trade of wild medicinal plants in the andean district of Lircay, Huancavelica, Perú: A comparative study - Castañeda, Roxana; Gutiérrez, Harol; Aponte, Héctor; Ocampo, Ivette Z.; Bussmann, Rainer W.; Paniagua-Zambrana, Narel Y. (Ethnobotany Research and Applications, 2021)
Introduction: Plants sold in public markets are important for the use and economic benefit they generate. This study documents the trade of wild medicinal plants in the district of Lircay, in the southern region of Peru. Additionally, the composition of the wild medicinal species registered in the study is compared with the richness of wild species reported in three markets in the region. Methods: The methodology was based on interviews with 70 vendors between 2015 and 2018. To compare the richness of species between markets, the data was conditioned in a matrix of presence and absence with which the Jaccard similarity index was calculated. Results and Discussion: Seventy-two wild medicinal plants were commercialized for 14 subcategories of medicinal use. The most frequently sold species were Clinopodium brevicalyx, Peperomia galioides and Minthostachys andina. It was also observed that the trade may be influencing the conservation status of Haplorhus peruviana and Ephedra rupestris, both taxa categorized as Critically Endangered according to Peruvian legislation. The problem of species replacement between Equisetum bogotense, Ephedra rupestris and Baccharis genistelloides, which are marketed under the name of "horsetail", is reported. Similarly, Perezia pinnatifida is sold under the common name of "valeriana" and is attributed the properties for the genus Valeriana. Those last observations suggest that an adequate taxonomic identification of the plants sold in public markets is necessary, specially, because of the antagonistic effects that could have different active ingredient of those species. Finally, when comparing the plants sold in Lircay with three other Andean markets (Ancash, Ayacucho and Huancavelica), a low similarity was found, which suggests a high variability of the commercialized plants and the need of more studies to know the total amount of species used for medicinal purposes in this region. Conclusions: The similarity of wild medicinal plants between the Andean markets of Cajamarca, Ancash, Ayacucho and Huancavelica is low. Keywords: Andes, trade, traditional knowledge, Huancavelica, medicinal plants, similarity. Resumen Introducción: Las plantas comercializadas en los mercados públicos son importantes por el uso y el beneficio económico que estas generan. El presente estudio documenta el comercio de plantas medicinales silvestres en el distrito de Lircay, en la región sur del Perú. Adicionalmente, se compara la composición de las especies medicinales silvestres registradas en el estudio con la riqueza de especies silvestres reportadas en tres mercados de la región. Métodos: La metodología se basó en entrevistas semiestructuradas realizadas a 70 vendedores entre los años 2015 y 2018. Para comparar la riqueza de especies entre mercados, los datos fueron acondicionados en una matriz de presencia ausencia con la cual se calculó el índice de similitud de Jaccard. Resultados y Discusión: Se reportaron 72 plantas medicinales silvestres comercializadas para 14 subcategorías de uso medicinal. Las especies con mayor frecuencia de venta fueron Clinopodium brevicalyx, Peperomia galioides y Minthostachys andina. Asimismo, se observó que el comercio podría influir en el estado de conservación de Haplorhus peruviana y Ephedra rupestris, ambas especies categorizadas En Peligro Crítico según la legislación peruana. Se reporta el problema de reemplazo de especies entre Equisetum bogotense, Ephedra rupestris y Baccharis genistelloides, las que son comercializadas bajo el nombre común de “cola de caballo”, de manera similar Perezia pinnatifida es comercializada bajo el nombre común de “valeriana” y se le atribuyen las propiedades conocidas para el género Valeriana. Lo que deja en evidencia la necesidad de una adecuada identificación taxonómica de las plantas comercializadas en los mercados públicos debido a los efectos antagónicos y tóxicos que podrían tener especies comercializadas bajo el mismo nombre común, pero con principios activos diferentes. Finalmente, al comparar la similitud entre las plantas expendidas en Lircay con otros tres mercados andinos (Cajamarca, Ancash y Ayacucho) se evidenció una baja similitud, lo que sugiere una alta variabilidad de las plantas comercializadas, y refuerza la necesidad de realizar más estudios para registrar e identificar la flora utilizada con fines medicinales en esta región. Conclusiones: La similitud de las plantas medicinales silvestres entre los mercados andinos de Cajamarca, Ancash, Ayacucho y Huancavelica es baja. Palabras clave: Andes, comercio, conocimiento tradicional, Huancavelica, plantas medicinales, similitud.